2023
DOI: 10.1007/s00240-023-01453-3
|View full text |Cite|
|
Sign up to set email alerts
|

Nedosiran in primary hyperoxaluria subtype 3: results from a phase I, single-dose study (PHYOX4)

Abstract: Nedosiran is an N-acetyl-D-galactosamine (GalNAc)–conjugated RNA interference agent targeting hepatic lactate dehydrogenase (encoded by the LDHA gene), the putative enzyme mediating the final step of oxalate production in all three genetic subtypes of primary hyperoxaluria (PH). This phase I study assessed the safety, pharmacokinetics (PK), and pharmacodynamics (PD) of subcutaneous nedosiran in patients with PH subtype 3 (PH3) and an estimated glomerular filtration rate  ≥ 30 mL/min/1.73 m2. Single-dose nedosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Approximately 27% of the administered nedosiran dose is excreted unchanged into the urine within 24 h of administration [ 7 ]. Nedosiran exposure in patients with PH3 is generally similar to that in those with PH1 or PH2 [ 13 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…Approximately 27% of the administered nedosiran dose is excreted unchanged into the urine within 24 h of administration [ 7 ]. Nedosiran exposure in patients with PH3 is generally similar to that in those with PH1 or PH2 [ 13 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…This therapy has been approved for treating primary hyperoxaluria type 1 (PH1) in adults and high oxalate levels in children aged 9 years and older. Studies have shown that nedosiran injections effectively lower 24-h urinary oxalate compared to placebo (Baum et al 2023 ; Goldfarb et al 2023 ). The therapy has proven to be well-tolerated and safe, with injection site reactions reported as the only common AE effects.…”
Section: Renal and Gastrointestinal Disordersmentioning
confidence: 99%
“…Treatments of PH3 that have been tested include substrate reduction therapy to target enzymes responsible production for oxalate with RNA interference (RNAi) (targeting LDH with Nedosiran) and CRISPR (targeting LDH) and enhanced intestinal oxalate degradation using probiotics (Oxalobacter formigenes) or enzymes (oxalate decarboxylase) ( Milliner et al, 2018 ; Lingeman et al, 2019 ; Quintero et al, 2020 ; Martinez-Turrillas et al, 2022 ; Goldfarb et al, 2023 ).…”
Section: Genetic Causes Of Nephrolithiasis and Nephrocalcinosis In Ch...mentioning
confidence: 99%